The relationship between ventricular electrical delay and left ventricular remodelling with cardiac resynchronization therapy - Gold, Michael R.; Birgersdotter-Green, Ulrika; Singh, Jagmeet P.; Ellenbogen, Kenneth A.; Yu, Yinghong; Meyer, Timothy E.; Seth, Milan; Tchou, Patrick J. (European heart journal, 2011)
Aims The aim of the present study was to evaluate the relationship between left ventricular (LV) electrical delay, as measured by the QLV interval, and outcomes in a prospectively designed substudy of the SMART-AV Trial. Methods and results This was a multicentre study of patients with advanced heart failure undergoing cardiac resynchronization therapy (CRT) defibrillator implantation. In 426 subjects, QLV was measured as the interval from the onset of the QRS from the surface ECG to the first large peak of the LV electrogram. Left ventricular volumes were measured by echocardiography at baseline and after 6 months of CRT by a blinded core laboratory. Quality of life (QOL) was assessed by a standardized questionnaire. When separated by quartiles based on QLV duration, reverse remodelling response rates (>15% reduction in LV end systolic volume) increased progressively from 38.7 to 68.4% and QOL response rate (>10 points reduction) increased from 50 to 72%. Patients in the highest quartile of QLV had a 3.21-fold increase (1.58-6.50, P = 0.001) in their odds of a reverse remodelling response after correcting for QRS duration, bundle branch block type, and clinical characteristics by multivariate logistic regression analysis. Conclusion Electrical dyssynchrony, as measured by QLV, was strongly and independently associated with reverse remodelling and QOL with CRT. Acute measurements of QLV may be useful to guide LV lead placement.